2016
DOI: 10.1177/1359105316648759
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies among patients newly diagnosed with diabetes or rheumatoid arthritis at baseline and after 24 months

Abstract: Patients aged 18-65 years with newly diagnosed diabetes mellitus ( n = 89) or rheumatoid arthritis ( n = 100) were studied by the General Coping Questionnaire at baseline and after 24 months. In total, 34 diabetes mellitus and 46 rheumatoid arthritis patients were diagnosed with psychosocial problems. The use of negative coping strategies, such as protest, isolation, and intrusion, was associated mostly with being classified as having psychosocial problems. With the risk of experiencing a strong impact of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
1
8
2
Order By: Relevance
“…Emotion-oriented coping strategies are associated with emotional disorders in a prospective study in diabetes subjects (Burns et al, 2016), as is passive coping for RA patients (Iaquinta and McCrone, 2015). In accordance with this, we found high scores on the coping strategy “protest” to predict both depression and anxiety (Gafvels et al, 2016). This finding was somewhat contradictory to the findings in a review on RA showing low evidence of an association between coping strategies and emotional well-being (Ramjeet et al, 2008).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Emotion-oriented coping strategies are associated with emotional disorders in a prospective study in diabetes subjects (Burns et al, 2016), as is passive coping for RA patients (Iaquinta and McCrone, 2015). In accordance with this, we found high scores on the coping strategy “protest” to predict both depression and anxiety (Gafvels et al, 2016). This finding was somewhat contradictory to the findings in a review on RA showing low evidence of an association between coping strategies and emotional well-being (Ramjeet et al, 2008).…”
Section: Discussionsupporting
confidence: 77%
“…Almost half of the RA patients (Gafvels et al, 2012), and more than one-third of the diabetes patients (Rane et al, 2011), were identified to need a psychosocial intervention at the time of the diagnosis of the disease, some due to financial constraints and others due to work-related issues. As regards coping strategies, RA patients showed lower scores on the coping strategy cognitive revaluation, and higher scores on protest and isolation, which is presented and discussed in a recent article (Gafvels et al, 2016). …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…On the basis of the aforementioned findings and the findings from our study, it can be thus assumed that employment is a kind of active coping with RA, which helps patients to tackle the feeling of helplessness, of being overwhelmed by the disease (Dixon et al, 2007; Gåfvels et al, 2018), and perhaps of being (also financially) dependent on others (Kochevar et al, 1997). Previous research strongly supports this assumption showing that learned helplessness predicted disability, pain, and fatigue at 2-year follow-up in RA patients (Camacho et al, 2013).…”
Section: Discussionmentioning
confidence: 55%
“…Such 13 coping is maladaptive and becomes a new source of stress. Research so far shows that passive coping correlates with increased pain, invalidity and depression (30).…”
Section: Discussionmentioning
confidence: 99%